ISOLASI DAN AMPLIFIKASI WILAYAH mtDNA D-LOOP PADA IKAN Kryptopterus limpok (Bleeker, 1852) DARI SUNGAI KAMPAR KIRI PROVINSI RIAU - Rizka Suci Akmando; Roza Elvyra; Dewi Indriyani Roslim (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
JOM FMIPA Volume 1 No. 2 Oktober 2014 224 ISOLASI DAN AMPLIFIKASI WILAYAH mtDNA D-LOOP PADA IKAN Kryptopterus limpok (Bleeker, 1852) DARI SUNGAI KAMPAR KIRI PROVINSI RIAU Rizka Suci Akmando, Roza Elvyra, Dewi Indriyani RoslimMahasiswa Program S1 Biologi Dosen Jurusan Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Kampus Bina Widya Pekanbaru, 28293, Indonesia rizkasuciakmando@yahoo.co.idABSTRACT Scientific information of mtDNA D-loop region in fish, Kryptopterus limpok, from Riau is unknown. Before having genetic information, total DNA isolation and amplification is necessary to be carried out. This study was aimed to obtain the total DNA molecules and DNA fragment of the mtDNA D-loop region in fish K. limpok from Sungai Kampar Kiri, Riau. Ten muscle samples were taken from fish collected from the river and used for total DNA isolation. Products of DNA isolation were amplified using the PCR technique with universal primers i.e. L15926 (F) 5’ TCA AAG CTT ACA CCA GTC TTG TAA ACC 3’ dan H00651 (R) 5’ TAA CTG CAG AAG GCT AGG ACC AAA CCT 3’. The PCR process consisted of pre-PCR at 940C for 5 minutes, 35 cycles of PCR consisted of three stages, i.e. as denaturation at 940C for 30 seconds, annealing at 590C for 1 minutes, elongation at 720C for 1 minutes, and post-PCR at 720C for 5 minutes. This study obtained the intact total DNA molecules, with the total DNA concentration of 100 μg/ μl. The length of mtDNA D-loop fragment was 153 bp.